2015
DOI: 10.1039/c5cc03114a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in purely organic phosphorescent materials

Abstract: Luminescent organic materials have attracted significant attention in recent times owing to their opportunities in various functional applications. Interestingly, unlike fluorescence, opportunities hidden within the phosphorescence properties of organic compounds have received considerably less attention even until last few years. It is only in the second decade of the 21st century, within a time span of less than last 5 years, that the concepts and prospects of organic compounds as phosphorescent materials ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
372
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(381 citation statements)
references
References 107 publications
7
372
0
2
Order By: Relevance
“…As described in the introduction to our paper, it has now been shown that organic solids with unusually short Br···Br interactions with phosphorescence lifetimes of milliseconds can be synthesized (Mukherjee and Thilagar, 2015; An et al , 2015; Gong et al , 2015; and Shi et al , 2016). Many of such compounds are described in the literature but have not been examined spectroscopically.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As described in the introduction to our paper, it has now been shown that organic solids with unusually short Br···Br interactions with phosphorescence lifetimes of milliseconds can be synthesized (Mukherjee and Thilagar, 2015; An et al , 2015; Gong et al , 2015; and Shi et al , 2016). Many of such compounds are described in the literature but have not been examined spectroscopically.…”
Section: Discussionmentioning
confidence: 92%
“…But more recently organic luminescent solids have received widespread attention; it has been shown that careful molecular design can be used to synthesize organic solids with phosphorescence lifetimes of milliseconds and longer (Mukherjee and Thilagar, 2015; An et al , 2015, Gong et al , 2015; and Shi et al , 2016). The solids are typically based on Br containing molecules with short Br···Br interactions.…”
Section: Introductionmentioning
confidence: 99%
“…化 学发光是指当 A 和 B 两种物质发生化学反应生成 C 物 质的同时释放出化学能, 该化学能被分子 C 或反应中间 态分子的电子吸收, 电子被激发到激发态, 并以发射光 子的形式释放出光能回到基态(图 1c) [35] . 相比以上三种 发光, 电致发光现象最晚被发现, 其原理是: 在外加电 场作用下, 电子和空穴分别从阴极和阳极向夹在电极之 间的有机功能薄膜层注进, 注进的电子和空穴在发光层 复合产生激子, 激子以辐射跃迁方式回到基态发出光的 过程(图 1d) [36] .…”
unclassified
“…1–3 Boron β–diketonates have the unique property of having strong emission in both solution and the solid state. 4,5 In solution, BF 2 bdks display large molar extinction coefficients, 6,7 two-photon cross-sections, 8,9 and high quantum efficiencies.…”
Section: Introductionmentioning
confidence: 99%